Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
Therefore, the solutions in simplified radical form are:
x = (17 + √65) / 16 or x = (17 - √65) / 16.
Step-by-step explanation:
To solve the equation 8x^2 - 17x + 7 = 0 using the quadratic formula, we can identify the coefficients a = 8, b = -17, and c = 7 in the general quadratic equation ax^2 + bx + c = 0.
The quadratic formula is x = (-b ± √(b^2 - 4ac)) / 2a.
Substitute the values of a, b, and c into the formula:
x = [17 ± √((-17)^2 - 4*8*7)] / 2*8
x = [17 ± √(289 - 224)] / 16
x = [17 ± √65] / 16
Therefore, the solutions in simplified radical form are:
x = (17 + √65) / 16 or x = (17 - √65) / 16.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.